Sculpting Nostalgia: Daniel Arsham, Alicja Kwade, and Kathleen Ryan - Ahn, J. (Intermédialités / Intermediality, 2022)
This article examines how the pace of technological progress has continued to accelerate the pace at which nostalgia is conjured and commodified. It undertakes a comparative study of sculptures by three contemporary artists, Daniel Arsham (USA, b. 1980), Alicja Kwade (Poland-Germany, b. 1979), and Kathleen Ryan (USA, b. 1984). While these three artists create and theorize in discretely different modes, their intermedial strategies are thematically linked in their shared leveraging of archaeological praxis and geological materiality vis-à-vis the temporal structure of nostalgia. Their sculptures are important case studies to unpack how nostalgia is culturally mobilized in this specific moment of technological acceleration and the resulting ecological perils of this progress.